Pengaruh Kecemasan Belajar terhadap Kemampuan Pemecahan Masalah Matematis Siswa Kelas IV Sekolah Dasar - Rosowati, Hidayah; Listiana; Rahmadhani , Mutiara; Amaliyah, Fitriyah (Papanda, 2025)
This study aims to analyze the effect of mathematics learning anxiety on the mathematical problem-solving abilities of fourth-grade students at SD Negeri 4 Karangbener. The population of the study consisted of all fourth-grade students at SD Negeri 4 Karangbener (14 students), with the sample selected through purposive sampling from the same population. The background of this study lies in the importance of problem-solving ability as a component of higher-order thinking skills and the significant role that anxiety can play as an affective factor potentially impeding the development of such abilities. This research employed a quantitative correlational approach using an ex post facto design. The instruments included a mathematics learning anxiety questionnaire and an essay test assessing problem-solving. Data were analyzed using simple linear regression with the aid of SPSS software. The results show that there is no significant effect of mathematics learning anxiety on students’ mathematical problem-solving ability (significance value = 0.966 > 0.05). These findings suggest that although students may experience anxiety during mathematics learning, it does not necessarily have a negative impact on their ability to solve problems. The study recommends that teachers continue to attend to affective aspects in learning and create a comfortable learning environment to optimally support students’ academic achievement.